2018
DOI: 10.3390/insects9040173
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Significance and Implications of Transovarial Transmission among the Vector-Borne Bunyaviruses: A Review

Abstract: Transovarial transmission (TOT) is a widespread and efficient process through which pathogens can be passed between generations of arthropod vectors. Many species within the order Bunyavirales utilize TOT as a means of persisting within the environment when classical horizontal transmission is not possible due to ecological constraints. The purpose of this review is to summarize previous findings regarding the ecological significance of TOT among viruses in the order Bunyavirales and identify the gaps in knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 100 publications
1
26
0
Order By: Relevance
“…However, some arboviruses have also evolved a means of vertical transmission whereby the virus is transmitted from parental arthropods directly to their offspring. Vertical transmission has been demonstrated among the bunyaviruses, flaviviruses, and alphaviruses indicating that this is a relatively common and convergent evolutionary strategy for virus persistence in the presence of ecological conditions that are not conducive to classical horizontal transmission [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some arboviruses have also evolved a means of vertical transmission whereby the virus is transmitted from parental arthropods directly to their offspring. Vertical transmission has been demonstrated among the bunyaviruses, flaviviruses, and alphaviruses indicating that this is a relatively common and convergent evolutionary strategy for virus persistence in the presence of ecological conditions that are not conducive to classical horizontal transmission [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arboviruses are predominantly transmitted horizontally (arthropod ↔ vertebrate), but when conditions are unfavorable (e.g., low numbers of susceptible hosts), arboviruses can also be maintained through other lower frequency mechanisms of transmission. Both field and laboratory studies have demonstrated that arboviruses from the genera Flavivirus and Orthobunyavirus can be maintained through vertical transmission (mother ↔ offspring) [ 21 , 22 ]. Interestingly, these studies have found that vertical transmission will only occur if an infected individual with a disseminated infection imbibes additional blood meals [ 23 ].…”
Section: Arbovirusesmentioning
confidence: 99%
“…From this, they estimated that LACV can persist four years or longer in the vector population in the absence of horizontal amplification in vertebrate hosts. Transovarial transmission (TOT) is ecologically significant in the persistence of many vector-borne pathogens and used frequently by members of Bunyavirales when classical horizontal transmission is not possible [29]. MIRs can be seen to be high in 2015 and 2016, reflecting that the small quantity of Ae.…”
Section: Discussionmentioning
confidence: 99%